Role of Legal Certainty in Providing Economic Security: Ukraine’s Experience - OSTAPENKO, Hanna (Theoretical and Practical Research in Economic Fields; Vol 14 No 2 (2023): TPREF, Volume XIV, Issue 2(28), Winter 2023, 2023)
Economic security is an element of the national security of the country. Even though regulation of economic security implies developing economic sectors or preventing threats, legal principles are not usually considered. The article analyzes how legal certainty as a principle forms a favorable environment, produces reliability, and encourages market players to realize their economic and entrepreneurial initiatives, provided that the country ensures a high level of it. A plurality of the elements of legal certainty makes the influence of the principle of legal certainty on the economic situation diverse and merely realized. It is proposed to divide these elements into two groups in the article. The first one consists of predictability, consistency, and stability. The second one incorporates the mechanisms, mostly legally provided, that prevent the violation of legal certainty. Further examples of court decisions and government acts show negative implications for economic security the violation of legal certainty can lead to. The stability that arises from legal certainty can help market players build their plans and calculate positive risks. Legal certainty contributes to the attraction of investments since profitability depends on the stability of legal regulation. Legitimate expectations are the components of the principle of legal certainty; they rely on the time an entrepreneur makes their business plans. Thus, the reliability that arises from respect to legitimate expectations plays a crucial role in long-term business planning. Immediate changes, the lack of enforcement caused by sudden changes in previously made decisions, and inconsistency in market management lead to a harmful economic effect on legitimate expectations.